Pectinase Production by Rhizopus stolonifer A3 Isolated from Apple Peels - Siti Lusi Arum Sari; Wida Puspa Tanjung; Klara Rizky Amilia; Ratna Setyaningsih; Artini Pangastuti (Caraka Tani: Journal of Sustainable Agriculture, 2023)
The application of pectinase in industries will continue to be developed. To broaden the applicability of enzyme manufacturing in new industries, more research to investigate pectinolytic microorganisms with high activity and stability is still required. Therefore, this study aimed to obtain pectinolytic fungi that have the potential as pectinase producers. Pectinolytic fungi were isolated from rotten apple peels and selected based on clear zone formation on pectic agar media after cetyl trimethyl ammonium bromide (CTAB) staining. Pectinolytic fungi were identified based on 18S rRNA partial gene sequences and morphological characteristics. Pectinase production used Mandels and Weber medium with citrus pectin 20 g l-1 addition. Pectinase activity was determined based on the measurement of reducing sugars by a colorimetric method. A total of 5 fungal isolates were successfully isolated. All of the isolates had pectinolytic activities with clear zone diameters ranging between 0.99 to 7.32 mm. The isolate A3 showing the highest pectinolytic activity was identified as Rhizopus stolonifer. Microscopically, R. stolonifer A3 showed typical characteristics for Rhizopus, characterized by the presence of rhizoids, stolons and sporangiophores bearing a single spherical sporangium. The pectinase production of R. stolonifer A3 was optimum at initial pH 5.0, temperature 35 °C and incubation period of 3 days with pectinase activity of 14.75 U ml-1. R. stolonifer A3 produced acidic pectinase having optimum activity at pH 5.0 and temperature 50 °C. Thus R. stolonifer A3 has the potential to be used as a producer of acidic pectinase appropriate for use in the processing of fruit products.